2021
DOI: 10.1088/1742-6596/1811/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of biomass combustion-basedstove byimplementing internally air-distribution

Abstract: This research aimed to enhance the performance of biomass combustion-based stove. Thermal performances were assessed in terms of power output (Pout), specific fuel consumption (SFC), thermal efficiency (ηth), and burning rate (BR). These performances were expected to meet the minimum standards established by the Indonesian biomass stove alliance regarding the use of a healthy and energy-saving of biomass stove in Indonesia. The stove tested was an improved stove with an advantage on the air distributor by addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The higher the ER, the higher the burning rate, means that more fuel is consumed. This finding is in accordance with what was found by Simanjuntak et al [24]. However, the high burning rate does not determine high temperatures of gas products.…”
Section: Data Representationsupporting
confidence: 93%
See 1 more Smart Citation
“…The higher the ER, the higher the burning rate, means that more fuel is consumed. This finding is in accordance with what was found by Simanjuntak et al [24]. However, the high burning rate does not determine high temperatures of gas products.…”
Section: Data Representationsupporting
confidence: 93%
“…By regulating the distribution of air in a wood-burning stove, Sornek, et al [22] and Carvalho et al [23] are also succeed in reducing greenhouse gas emissions. By placing an air distributor concentrically in a cylindrical biomass combustor, Simanjuntak, et al found that the temperature of the flame reach of about 550 o C [24]. Caposciutti et al [25] also studied fixed-bed combustor for commercial scale boiler by varying excess air to control the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the fluidized bed reactor can be scaled to an industrial scale [38]. Whereas, the packed bed reactor also has high performance when the hydrodynamic flow of combustion air is made more evenly distributed [39][40]. In pyrolysis, there are three heating methods that are always used by researchers; the fast, medium, and slow heating methods.…”
Section: Fig 2 Parameters Related To the Popw Production Qualitymentioning
confidence: 99%
“…Stove technology refers to the use of specialized stoves or furnaces to safely and efficiently combust waste materials. The number of stoves that have been tested related to their function intended to collect and collate information about performances and their output in the form of energy and emission parameters [7], [8]. This technology aims to minimize the environmental and health risks associated with especially hazardous waste energy recovery.…”
Section: Introductionmentioning
confidence: 99%